Mast Cells Modulate Acute Toxoplasmosis in Murine Models - Huang, Bo (Public Library of Science, 2013)
The role of mast cells (MCs) in Toxoplasma gondii infection is poorly known. Kunming outbred mice were infected intraperitoneally with RH strain T. gondii, either treated with compound 48/80 (C48/80, MC activator) or disodium cromoglycate (DSCG, MC inhibitor). Compared with infected controls, infected mice treated with C48/80 exhibited significantly increased inflammation in the liver (P < 0.01), spleen (P < 0.05), and mesentery (P < 0.05) tissues, higher parasite burden in the peritoneal lavage fluids (P < 0.01), and increased levels of mRNA transcripts of T. gondii tachyzoite surface antigen 1 (SAG1) gene in the spleen and liver tissues (P < 0.01), accompanied with significantly increased Th1 cytokine (IFN-γ, IL-12p40, and TNF-α) (P < 0.01) and decreased IL-10 (P < 0.01) mRNA expressions in the liver, and increased IFN-γ (P < 0.01) and IL-12p40 (P < 0.01) but decreased TNF-α (P < 0.01) and IL-4 (P < 0.01) in the spleens of infected mice treated with C48/80 at day 9-10 p.i. Whereas mice treated with DSCG had significantly decreased tissue lesions (P < 0.01), lower parasite burden in the peritoneal lavage fluids (P < 0.01) and decreased SAG1 expressions in the spleen and liver tissues (P < 0.01), accompanied with significantly increased IFN-γ (P < 0.01) and IL-12p40 (P < 0.05) in the liver, and decreased IFN-γ (P < 0.05) and TNF-α (P < 0.01) in the spleens; IL-4 and IL-10 expressions in both the spleen and liver were significantly increased (P < 0.01) in the infected mice treated with DSCG. These findings suggest that mediators associated with the MC activation may play an important role in modulating acute inflammatory pathogenesis and parasite clearance during T. gondii infection in this strain of mice. Thus, MC activation/inhibition mechanisms are potential novel targets for the prevention and control of T. gondii infection.